Health impact of borders: general reflections and a case study from the Polish–German border - Julia Kuntosch; Marie-Luise Ruebsam; Jakub Orsson; Dorota Orsson; Klaus Hahnenkamp; Jörg Hartleib; Steffen Flessa (The European Journal of Health Economics, 2023)
Abstract Background and objective Political, economic, communicative and cultural borders still limit the accessibility of acute healthcare services for patients so that they frequently have to accept longer distances to travel to the next provider within their own country. In this paper, we analyze the impact of borders and opening of borders on acute medical care in hospitals and on patients in border regions. Methods We develop a conceptual framework model of cross-border healthcare and apply it to the Polish–German border area. The model combines the distance decay effect, a catchment area analysis, economies of scale and the learning curve. Results Borders have a major impact on acute medical care in hospitals and on patients. Setting of new borders will reduce the accessibility of health facilities for patients or require the establishment of new hospitals. Reopening borders might induce a vicious circle leading to the insolvency of a hospital which might result in poorer health for some patients. Conclusion Strong effort should be invested to overcome political and cultural borders to improve the health of the population in border regions. Similarly, increased cross-border acute healthcare must be seen in the context of rural health and the special situation of small rural hospitals in rural peripheral areas.
Keywords: 330; Border; Catchment area; Cross-border healthcare; Distance decay effect; Polish–German border area